Teacher-Student Relationships: Understanding the Impact on Science Students’ Academic Performance from Both Sides of the Classroom - Nwafor, Stephen Chinedu; Kanu, Mavis Obianuju; Ekoyo, Destiny Onyebuchi; Nwankwo, Maryjane Uche (RADINKA JAYA UTAMA PUBLISHER, 2025)
The study investigated the impact of student-teacher relationships on science students’ academic performance in computer studies in Awka South Local Government Area. A descriptive survey research design was adopted. The population size comprised all the science teachers and students in the 50 secondary schools in Aguata Education Zone of Anambra State, Nigeria. 60 science teachers and 300 science students were randomly sampled while a questionnaire was used for data collection. Data collected were analyzed using mean, standard deviation and t-test. The findings of the study revealed that both the students and teachers agreed that cordial relationship between them influences students’ academic performance. Also, cordial relationship among teachers and science students in secondary schools in Aguata Education Zone is to a low extent. The factors affecting cordial relationships between teachers and science students in secondary schools include students’ hatred of their teachers, laziness, students’ unwillingness to do their take-home assignments and establish good relationships with the students, and truancy. Furthermore, the possible solutions to the factors affecting teacher-student relationships in secondary schools are that teachers should use student-centered teaching methods and avoid flogging as the only means to discipline the students among others. Therefore, the researchers recommended among others that there is a need for science teachers to create a conducive environment that will develop, enhance and sustain good relationships with their students towards better academic performance.